Alignment of Rod‐Shaped Single‐Photon Emitters Driven by Line Defects in Liquid Crystals. (6th February 2015) - Pelliser, Laurent; Manceau, Mathieu; Lethiec, Clotilde; Coursault, Delphine; Vezzoli, Stefano; Leménager, Godefroy; Coolen, Laurent; DeVittorio, Massimo; Pisanello, Ferruccio; Carbone, Luigi; Maitre, Agnes; Bramati, Alberto; et al.
Abstract : Arrays of liquid crystal defects—linear smectic dislocations—are used to trap semiconductor CdSe/CdS dot‐in‐rods which behave as single‐photon emitters. Measurements of the emission diagram are combined together with measurements of the emitted polarization of the single emitters. It is shown that the dot‐in‐rods are confined parallel to the linear defects to allow for a minimization of the disorder energy associated with the dislocation cores. It is demonstrated that the electric dipoles associated with the dot‐in‐rods, tilted with respect to the rods, remain oriented in the plane including the smectic linear defects and perpendicular to the substrate, most likely due to dipole/dipole interactions between the dipoles of the liquid crystal molecules and those of the dot‐in‐rods. Using smectic dislocations, nanorods can consequently be oriented along a unique direction for a given substrate, independently of the ligands' nature, without any induced aggregation, leading as well to a fixed azimuthal orientation for the dot‐in‐rods' dipoles. These results open the way for the fine control of nanoparticle anisotropic optical properties, in particular, fine control of single‐photon emission polarization. Abstract : The self‐alignment of CdSe/CdS dots‐in‐rods is realized through their deposition within aligned line defects of smectic liquid crystals. The measurements of numerous single‐photon emitters evidences, for a given liquid crystal film, a unique alignment of the in‐plane dipoles associated with these particles. Fine control of the polarization of single photons emitters is thus achieved.